2019
DOI: 10.3390/molecules24224199
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lactoferrin in Camel Milk by Ultrahigh-Performance Liquid Chromatography-Tandem Mass Spectrometry Using an Isotope-Labeled Winged Peptide as Internal Standard

Abstract: An ultrahigh-performance liquid chromatography-tandem mass spectrometry method was developed and validated for the determination of lactoferrin in camel milk based on the signature peptide. The camel lactoferrin was purified by heparin affinity chromatography and then used to screen tryptic signature peptides. The signature peptide was selected on the basis of sequence database search and identified from the tryptic hydrolysates of purified camel lactoferrin by ultrahigh-performance liquid chromatography and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…CM has higher lactoferrin content than milk from cows, goats, and buffaloes. 34 A study revealed that lactoferrin could increase the survival rate of mice exposed to X-ray irradiation by decreasing the levels of serum IL-6 and TNF-a and reducing the expression of radiation-induced IKKa/b and NF-kB. 19 In conclusion, our findings demonstrated that CM reduces the level of inflammatory cytokines by regulating the HMGB/ TLR4/NF-kB/MyD88 pathway and the antioxidant capacity to decrease radiation-induced intestinal damage (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CM has higher lactoferrin content than milk from cows, goats, and buffaloes. 34 A study revealed that lactoferrin could increase the survival rate of mice exposed to X-ray irradiation by decreasing the levels of serum IL-6 and TNF-a and reducing the expression of radiation-induced IKKa/b and NF-kB. 19 In conclusion, our findings demonstrated that CM reduces the level of inflammatory cytokines by regulating the HMGB/ TLR4/NF-kB/MyD88 pathway and the antioxidant capacity to decrease radiation-induced intestinal damage (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…CM has higher lactoferrin content than milk from cows, goats, and buffaloes. 34 A study revealed that lactoferrin could increase the survival rate of mice exposed to X-ray irradiation by decreasing the levels of serum IL-6 and TNF-α and reducing the expression of radiation-induced IKKα/β and NF-κB. 19 …”
Section: Discussionmentioning
confidence: 99%
“…e sample extract was added after treatment with the buffer. After the sample solution was eluted completely, the column was rinsed with 10 [22]. e eluent was collected and centrifuged at 9000 rpm for 5 min before UPLC analysis.…”
Section: Sample Cleanupmentioning
confidence: 99%
“…Camel milk whey proteins, caseins, and LAB have been the subject of a number of studies looking at their potential antioxidant, immune-regulating, anti-inflammatory, and anti-microbial effects. Antioxidant properties were found in camel milk in all studies [4,5]. The oxidation reaction in foods is one of the most difficult challenges facing the food and medical sciences because it is directly related to food safety and consumer health.…”
Section: Introductionmentioning
confidence: 98%